A interface da notícia nos meios impresso e digital: o tratamento da notícia nas primeiras páginas dos jornais impressos e portais na internet - Bekesas, Wilson Roberto (2006)
It was intended to discuss questions about the characteristics of digital and printed media related to the way of publishing the news on the first pages of newspapers and web portals on the Internet. The news is presented as an object and it has as a sign the interface inside the media mentioned above. Both present approaches on the treatment of information about their projects and on their construction. A matrix involving the objects of research selected here is presented so that it can compare both. The first pages of newspapers O Estado de S. Paulo and Folha de S. Paulo and the web portals UOL and Terra have been taken into account. Some history aspects of the two media and their characteristics will be analyzed. Beside that, mediation processes and the construction of the interface, the diagrammatic relation between the media; their spatiality and visibility. During the development of this research, it has been discussed questions related to the transition of the part of the interpreter as a reader, as a user and later as a knowledge navigator, which has taken our research question to the edges of a process in constant evolution: the own human being action in the construction of knowledge in technological extensions